The Western Sahara conflict in the Spanish press: analysis of the Van Walsum episode - Soriano Forte, Ginés (Estudios sobre el Mensaje Periodístico, 2012)
Due to its origin and the social interest it generates, the extensive conflict over the former Spanish Sahara has a much bigger informative interest in Spain than in any other western country. Is Spanish press able to set up its own international agenda-setting about this especially close foreign news? The resignation of the UN special delegate, Peter Van Walsum, after a controversial comment about the future of this dispute has been an especially relevant moment in the Western Sahara conflict. This article is an analysis of the coverage of that episode, including possible biased information, given by four Spanish newspapers (ABC, El Mundo, Público, and specially El País) and another one from Morocco (Le Matin), as external reference.
Keywords: international agenda-setting; conflict; Western Sahara; Spanish press; publishing line